THE BEST PRACTICE OF INTEGRATING HOTS (HIGH ORDER THINKING SKILL) IN ENGLISH FOR PHARMACY CLASS AT QAMARUL HUDA BADARUDDIN UNIVERSITY - Hasbullah Hasbullah; Baiq Hardia Martanti; Sulistyahadi Sulistyahadi; Fauziyatun Ni'mah; Lalu Muhamad Busroni (Bajang Institute, 2022)
Integrating HOTS (high order thinking skill) in EFL classes is one of the interesting and important issues in the context of teaching English in order to improve the students’ creativity and make them create their own innovation in the process of learning English in the class. Based on Bloom’s revised taxonomy that the educators (teacher or lecturer) are not only encouraged to teach four skills in language teaching (speaking, reading, writing, and listening) the writer just focuses on Integrating HOTS (high order thinking skill) in English for pharmacy class. As we know that there are four skills of English (listening, reading, speaking, and writing.) which should be mastered by students in the process of learning English, whereas the lecturer are required to be able to integrated high order thinking skill (HOTS) in English for pharmacy class. Integrating HOTS in English for pharmacy class through video focus on the four skills of English (listening, reading, speaking, and writing skill). Through video, the lecturer can measure students’ ability in listening, reading, speaking, and writing skill.